KEBERADAAN KOPERASI JAYA PELITA BAGI MASYARAKAT DI KELURAHAN PANGOLOMBIAN KOTA TOMOHON SULAWESI UTARA - Deisy A. P. J. Pangkey (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Abstract. The existence of Jaya Pelita Cooperative in Pangolombian Village, Tomohon Selatan, Tomohon, and its benefits to the community. The cooperative is one of the solutions so that people can develop their business by borrowing money from the cooperative, although with a relatively large interest rate and high administrative costs, it is still attractive to the community because of the easy requirements. This research uses a qualitative method. The results of the research obtained from interviews conducted with several customers include; cooperatives are very helpful for those who need funds to open a business and meet family needs, and cooperative loans are used for daily needs. Based on the results of the research, it can be concluded that the existence of Jaya Pelita Cooperative is very helpful to the people of Pangolombian Village. Researchers suggest that the Cooperative should not provide admin fees and interest fees that are too high for customers. The researcher hopes that by reading this article, other researchers will be motivated and inspired to conduct other research to make a positive contribution to other communities.